Political Parties and Trading in Influence: A Comparative Study from a Civil Law Perspective in Indonesia and Sri Lanka - Ali, Hilmy Faidulloh; Djatmika, Prija; Yuliati, Yuliati; Istiqomah, Milda (Batulis Civil Law Review, 2026)
Introduction: The phenomenon of trading in influence is a form of political corruption that is difficult to identify because it operates within the realm of power relations that do not always take the form of direct bribery. Political parties in the context of modern democracies often act as mediators between public and economic interests, making them potentially key actors in the practice of trading in influence.Purposes of the Research: This study aims to analyze the involvement of political parties in the practice of trading in influence and compare the effectiveness of regulations and law enforcement in Indonesia and Sri Lanka. Furthermore, this study examines the extent to which the civil legal systems in both countries are able to close legal loopholes that allow for covert political corruption.Methods of the Research: This research uses a normative legal method with a comparative approach, examining legislation, jurisprudence, and international documents related to political corruption. Secondary data was obtained through a study of academic literature, reports from anti-corruption agencies, and a comparative analysis of the implementation of the United Nations Convention Against Corruption (UNCAC) in both jurisdictions, namely Indonesia and Sri Lanka.Results / Main Findings / Novelty/Originality of the Research: The results show that Indonesia and Sri Lanka face similar challenges in enforcing laws against influence peddling due to weak regulations explicitly addressing the practice. However, Indonesia has shown progress in adopting the principles of the United Nations Convention Against Corruption (UNCAC), while Sri Lanka remains limited to an administrative approach without strong criminal sanctions.